ANALISYS OF THE INFLUENCE OF COMMUNICATION PARAMETERS OF FSO CHANNELS ON THE RECEPTION QUALITY - Marković, Aleksandar; Panić, Stefan; Jakšić, Branimir; Spalević, Petar; Smilić, Marko (Bulletin of Natural Sciences Research, 2017)
In this paper, the signal transmission in the Free-Space Optics (FSO) communication system using the software package OptiSystem 7.0 is analyzed. The influence of parameters FSO (Free-Space-Optics) channels (Range, Attenuation, Beam Divergence, Transmitter Loss, Receiver Loss, and Additional Losses) on the reception quality is considered. The reception quality is analyzed according to the values of BER (Bit Error Ratio) and Q factor. Graphics and tables of the changes of BER and Q factor depending on the parameters of FSO are given. Also, the eye diagrams for the characteristic parameter values are given.